Acetonitrile-assisted exfoliation of layered grey and black arsenic: contrasting properties - Antonatos, Nikolas; Mazánek, Vlastimil; Lazar, Petr; Sturala, Jiri; Sofer, Zdeněk (Nanoscale advances, 2020)
In recent years, two-dimensional monoelemental nanostructures beyond graphene have received great attention due to their outstanding properties. Out of these elements, only arsenic is known to form different allotropes with a layered structure in the bulk form. Orthorhombic arsenic, also termed "black arsenic", is a metastable form of arsenic with a structure analogous to that of black phosphorus and rhombohedral arsenic is known as "grey arsenic". Here, we compare the exfoliation of black and grey arsenic in acetonitrile in high yield forming stable colloidal solutions of exfoliated materials. Together with the exfoliation procedure, detailed structural and chemical analyses are provided and potential applications in gas sensing and photothermal absorption are demonstrated for potential future arsenic-based devices.